Role of footwear allergens in juvenile plantar dermatosis - Perumbil, Shyni; Muhammed, Kunnummal; Sasidharan Pillai, Sarita (International Journal of Research in Dermatology, 2017)
Background: Juvenile plantar dermatosis (JPD) is characterized by shiny dry fissured dermatitis of the plantar surface of the foot, affecting children aged 3-14years. The most accepted theory is that JPD is a frictional contact dermatitis of the forefoot in which atopics are more prone to develop. Allergic contact dermatitis remains a close differential diagnosis; it can aggravate the predisposing JPD. In this background we carried out a study among children aged fourteen years and below with clinically diagnosed JPD to know the age and sex profile, aggravating factors and clinical features in this part of the country. Methods: All children aged 14 years and below with JPD attending our outpatient department from November 2006 to November 2007 were included in this study. Using a preset proforma, data regarding age and sex, information on any relation to footwear, past history of allergic disorders in person or family members was collected. All the 40 patients were patch tested using the footwear allergen series in petrolatum base. Patch test unit was removed after 48hours and the results were interpreted using criteria laid down by International Contact Dermatitis Group (ICDRG). The data was analyzed and made an attempt to understand the role of footwear allergy in JPD. Results: 22 girls and 18 boys attended our OPD with JPD between the age group of 4-14 years. 52.5% were using footwear made of plastic; 25%used leather; 12.5% rubber footwear. Patients presented with erythema and glazed appearance of foot along with fissuring. The areas of involvement were distal soles and toes in 70%, distal sole alone in 7.5% and distal sole and dorsum of toes in 22.5% of patients. Personal history of atopy was documented in 15% of patients and family history of atopy was present in 20% of cases. 20% of patients complained of exacerbation with footwear. Of the 40 patients who underwent patch testing, 10% only showed positive patch test reaction mainly to potassium dichromate (5%). Conclusions: JPD is not an uncommon disease and it predominantly affects school going children. Seasonal variation was associated with aggravation of disease. Specific footwear was identified to cause flare ups in a significant percentage of study population (20%) and this was proven by patch test results in half of them. Though nearly one fifth of the affected had an atopic diathesis in person or family, the present data suggests that JPD is not exclusive to atopics. A large sized study is required to evaluate the role of footwear in JPD.